2014
DOI: 10.3748/wjg.v20.i33.11886
|View full text |Cite
|
Sign up to set email alerts
|

S-1-basedvsnon-S-1-based chemotherapy in advanced gastric cancer: A meta-analysis

Abstract: S-1-based chemotherapy may be a good choice for AGC because of longer survival times, better tolerance and more convenient use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The data in the current study do not therefore suggest any relevant change to the established safety profile of S-1, with no new safety concerns apparent for the EOS combination. Highlighting the potential of S-1 in this setting, a recent meta-analysis which compared S-1 based with non-S-1-based chemotherapy in the first-line Phase I study of orally administered S-1 in combination with epirubicin and oxaliplatin in… 365 treatment of advanced gastric cancer showed that S-1-based regimens were associated with higher objective response rates, longer overall survival, longer time-totreatment failure, and lower risks of febrile neutropenia and stomatitis [31]. In summary, the encouraging activity of the EOS regimen observed in this study, along with an acceptable safety profile, supports further clinical development of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…The data in the current study do not therefore suggest any relevant change to the established safety profile of S-1, with no new safety concerns apparent for the EOS combination. Highlighting the potential of S-1 in this setting, a recent meta-analysis which compared S-1 based with non-S-1-based chemotherapy in the first-line Phase I study of orally administered S-1 in combination with epirubicin and oxaliplatin in… 365 treatment of advanced gastric cancer showed that S-1-based regimens were associated with higher objective response rates, longer overall survival, longer time-totreatment failure, and lower risks of febrile neutropenia and stomatitis [31]. In summary, the encouraging activity of the EOS regimen observed in this study, along with an acceptable safety profile, supports further clinical development of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…Six meta-analyses compared S-1-based therapy with 5-FU-based therapy [7, 14, 19, 21, 24, 42]. Five of them compared OS [7, 14, 19, 24, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Five of them compared OS [7, 14, 19, 24, 42]. Among them, four of them favored S-1-based therapy [14, 19, 24, 42] while one meta-analysis showed that there was no statistically difference between two groups in terms of OS [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations